Paleoseismicity evidence in the region of lima (peru central coast) - Jacay Huarache, Javier Pablo (2013)
Data on natural disasters of this part of the Andean margin, is only known since the earliest records of the chronicles written by the Spaniards in the conquest stage, this data has served to cataloging the major earthquakes and ENSO relatioships. The study of paleoseismicity require the application of classical geology concepts to the last deformation phase, the morphotectonic features or deformation generated by strong earthquakes or gradual tectonic deformation occurred in this particular case during the Pliocene-Quaternary. For the Lima area there is the identification and characterization of sedimentary structures generated by the seismic effect known as seismites, which correspond to unconsolidated fluvio torrential deposits, lacustrine deposits, amongst others; these deposits have a relative abundance of sedimentary structures linked to seismic events, the most common structures are the contoured layers (wavy lamination) or invaginations, load structures and injections of sand and/or clay. With the data collected we can make an outline of the relative chronology for events happened in the fluvial-alluvial valley of Rimac River.